O bem-estar no trabalho e suas relações com suporte e comprometimento organizacional: estudo de caso na Universidade Federal de Santa Maria(UFSM) - Bizzi, Luciane (2013)
The well-being of workers has been perceived by managers as a fundamentally strategic aspect, since that, interfering on the professional behavior (LOCKE, 1976), tends to impact on the quality in the provision of services and the achievement of results and organizational goals (DAVIS, NEWSTROM, 2001). Understanding the context of the strategic management of public organizations in face of current challenges and considering the shortage of studies on the IES in question about: (i) the labor activity as a source of positive experiences, (ii) the perception of organizational reciprocity and (iii) potencial implications in a conduct more responsive with the excellence in public service, the proposal of this research lies in the following question: What is the level of well-being at work of the UFSM s technical-administrative officials and what are the relations with support and organizational commitment? . To answer this question, are used 3 theoretical models: the model suggested by Paschoal and Tamayo (2008) to evaluate well-being at work; the model suggested by Siqueira (2005) to measure organizational support and the the model suggested by Medeiros and Enders (1998) for organizational commitment, exclusively its affective dimension. This is a quantitative research, whose data are submitted to statistical methods and it‟s categorized as a case study of micro-organizational dimension. The sample was composed for 332 collaborators, distributed on the three levels of career (fundamental, middle and higher) and allocated in the eight Education Centers of the UFSM‟s main campus and Rectory. Although heterogeneous, the sample in its majority was composed for officials with 43 years of age, 16 years working at the UFSM, family income of approximately R$ 7.000,00, specialists, married and with child (children). The statistical analyzes showed that the intensity of self-perceived well-being at work achieved a level of neutrality. On the other hand, the self-perception about organizational support revealed a negative evaluation at a low level and the self-perception about affective organizational commitment revealed neutrality in the opinions of the respondents. The predetermined hypothesis in the research were confirmed, which reveals that 14,7% of the affective commitment is positively impacted by the well-being, 26% of the well-being is positively impacted by the perceived organizational support and 10,4% of the affective commitment is positively impacted by the perceived organizational support. In managerial terms, the realization of this research contributes as a as a possible diagnosis that expands the horizons of scientific knowledge about behavioral aspects in socio-organizational context of public institutions.